(3GdEfSGf GdcGed aj eYQaI GdChGNQ hGdChGFds - (3YHO GdcQje Hf EHQGgje Hf YHO GdcQje GdLjdj GdUhaj , bWH GdOjf,J (B832 (3g` s
(3ChdgG (B:s
(3GdMeO ddg def bGe HMeOg GSe Gddg CeG HYO aEfg deG cGf ceGd GdEfSGf ai GdYde HGddg haVdg Ydi LfSg HbOQ eG GcJSH ef aMhGg s
(3BNQgG (B:s
(3Ef GdhSjdI CYdG ecGf ai GdLfI hdG Jchf EdG dhGMO aCQLh Cf Gchf Pdc GdQLd dCfg cGf dg GdHOA ai GdhLhO adG HO Cf jchf dg GdNJGe Ydjg CaVd GdUdGI hGdSdGe s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B50 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B313s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs